Online shopping site selection attributes and meta tags: an empirical analysis. (21st February 2022) - Sharma, Rahul; Verma, Rajesh; Mehta, Megha
With the availability of better information technology infrastructure in India, there are many national and global online shopping sites that have started to emerge in the Indian online shopping front. India, with 400 million internet users, is the world's second largest internet market and the e-commerce market of India is projected to touch 84 billion by the year 2021. The need of the hour is to identify attributes of shopping sites that play part in shaping consumer's online platform selection intention and also to access the understanding of online shopping site about customer preferences. Prior studies have investigated factors that affect the preference of consumers towards e-retail websites but what attributes of e-retailers attract them to use such services is still an unexplored area. Meta tag analysis of the major online retailers will help in the assessment of the online retailer's knowledge of customer preferred attributes. This study will help e-retailers to understand the kind of attributes that are preferred by customers in selecting a website for online shopping and where do online retailers stand in exploiting consumer preferences in their search engine optimisation efforts.